Euthanasia - Haneef, Sayed Sikandar Shah (Oxford University Press, 2017)
Islam attaches utmost sanctity to human life. Its inviolability is guaranteed not only against the aggression by an outside assailant but also the person himself/herself except as justified by Islamic law. Accordingly, both homicide and suicide are prohibited in Islam. Advancements in the field of medicine, however, have created a new way of ending the life of a patient either on his/her own initiative or if a treating physician deems it fit to discontinue futile medical care, which is called euthanasia. This entry aims to present a compact view of Islamic juridico-ethical stand on the issue.